Written Pain Neuroscience Education in Fibromyalgia: A Multicenter Randomized Controlled Trial. Issue 8 (20th November 2013) - van Ittersum, Miriam W.; van Wilgen, C. Paul; van der Schans, Cees P.; Lambrecht, Luc; Groothoff, Johan W.; Nijs, Jo
Abstract Mounting evidence supports the use of face‐to‐face pain neuroscience education for the treatment of chronic pain patients. This study aimed at examining whether written education about pain neuroscience improves illness perceptions, catastrophizing, and health status in patients with fibromyalgia. A double‐blind, multicenter randomized controlled clinical trial with 6‐month follow‐up was conducted. Patients with FM (n = 114) that consented to participate were randomly allocated to receive either written pain neuroscience education or written relaxation training. Written pain neuroscience education comprised of a booklet with pain neuroscience education plus a telephone call to clarify any difficulties; the relaxation group received a booklet with relaxation education and a telephone call. The revised illness perception questionnaire, Pain Catastrophizing Scale, and fibromyalgia impact questionnaire were used as outcome measures. Both patients and assessors were blinded. Repeated‐measures analyses with last observation carried forward principle were performed. Cohen's d effect sizes (ES) were calculated for all within‐group changes and between‐group differences. The results reveal that written pain neuroscience education does not change the impact of FM on daily life, catastrophizing, or perceived symptoms of patients with FM. Compared with written relaxation training, written pain neuroscience education improved beliefs in a chronic timeline of FM (P = 0.03; ES = 0.50), but it does not impact upon other domains of illness perceptions. Compared with written relaxation training, written pain neuroscience education slightly improved illness perceptions of patients with FM, but it did not impart clinically meaningful effects on pain, catastrophizing, or the impact of FM on daily life. Face‐to‐face sessions of pain neuroscience education are required to change inappropriate cognitions and perceived health in patients with FM.